Dead Battery? Wind Power, the Spot Market, and Hydro Power Interaction in the Nordic Electricity Market - Johannes Mauritzen (Research Institute of Industrial Economics (IFN), 2012)
It is well established within both the economics and power system engineering literature that hydro power can act as a complement to large amounts of intermittent energy. In particular hydro power can act as a battery where large amounts of wind power are installed. In this paper I use simple distributed lag models with data from Denmark and Norway. I find that increased wind power in Denmark causes increased marginal exports to Norway and that this effect is larger during periods of net exports when it is difficult to displace local production. Increased wind power can also be shown to slightly reduce prices in southern Norway in the short run. Finally, I estimate that as much as 40 percent of wind power produced in Denmark is stored in Norwegian hydro power magazines.
Keywords: L90; Q40; 330; Wind Power; Hydro Power; Nordic Electricity Market; Empirical; Windenergie; Wasserkraft; Energiehandel; Energiepreis; Norwegen; Dänemark